2021
DOI: 10.3390/nano11102540
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Silver Nanoparticles: Study of the Chemical and Molecular Structure, and the Ability to Interact with Cadmium and Arsenic in Water and Biological Properties

Abstract: In the field of research for designing and preparing innovative nanostructured systems, these systems are able to reveal the presence of heavy metals in water samples, and can efficiently and selectively interact with them, allowing for future applications in the field of water remediation. We investigated the electronic and molecular structure, as well as the morphology, of silver nanoparticles stabilized by mixed biocompatible ligands (the amino acid L-cysteine and the organic molecule citrate) in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Overall, adding this stabilization solution had no significant impact on the plasmonic spectrum of silver nanoplates, which means that their nanostructure remains preserved at all concentrations following the immediate addition of the stabilization solution. Still, a minor wavelength shift of the main plasmonic band is observed and displayed in Figure C (green diamonds), a general feature of thiol adsorption on metallic nanoparticles . Strikingly, the wavelength first increases (red-shift) and then decreases (blue-shift) upon increasing the thiol concentration.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, adding this stabilization solution had no significant impact on the plasmonic spectrum of silver nanoplates, which means that their nanostructure remains preserved at all concentrations following the immediate addition of the stabilization solution. Still, a minor wavelength shift of the main plasmonic band is observed and displayed in Figure C (green diamonds), a general feature of thiol adsorption on metallic nanoparticles . Strikingly, the wavelength first increases (red-shift) and then decreases (blue-shift) upon increasing the thiol concentration.…”
Section: Resultsmentioning
confidence: 89%
“…Still, a minor wavelength shift of the main plasmonic band is observed and displayed in Figure 2 C (green diamonds), a general feature of thiol adsorption on metallic nanoparticles. 18 Strikingly, the wavelength first increases (red-shift) and then decreases (blue-shift) upon increasing the thiol concentration. Interestingly, this nonmonotonic behavior is also observed when plotting the long-term change of transmittance as also shown in Figure 2 C (blue dots).…”
Section: T H Imentioning
confidence: 99%
“…To this aim, two types of AgNPs, one functionalized with citrate and L-cysteine (AgNPcitLcys) and the other one with sodium-3-mercapto-1propanesulfonate (AgNP3MPS), both developed as sensors for metal ions (i.e., mercury and nickel) in water media, were fully characterized in different exposure media and tested. [24][25][26][27] Unicellular microorganisms, such as Gramnegative bacteria Escherichia coli, freshwater microalgae Raphidocelis subcapitata and marine microalgae Phaeodactylum tricornutum and mammalian cells (HeLa, L929), were selected for investigating the mechanism of (eco) toxicity along with transformation occurring in exposure media and bio-nano-interactions.…”
Section: Introductionmentioning
confidence: 99%
“…, mercury and nickel) in water media, were fully characterized in different exposure media and tested. 24–27 Unicellular microorganisms, such as Gram-negative bacteria Escherichia coli , freshwater microalgae Raphidocelis subcapitata and marine microalgae Phaeodactylum tricornutum and mammalian cells (HeLa, L929), were selected for investigating the mechanism of (eco)toxicity along with transformation occurring in exposure media and bio–nano-interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the thiol group containing amino acid could easily modify the surface sites of the NPs. [22][23][24] The objective of the present investigation is to establish a corona complex using AgNPs with a suitable biomolecule for selective determination of bioactive compounds. To progress this work, the AgNPs have been synthesized with different amino acids, including cysteine (Cys), glutamine (Glu), glutathione (GSH), glycine (Gly), leucine (Leu), methionine (Meth), tyrosine (Tyr), and valine (Val), to form amino acid coronas, which were then exposed to other organic acids, such as citric acid, succinic acid and tartaric acid.…”
Section: Introductionmentioning
confidence: 99%